Núcleo integral de atención psicologica (2022)
The Comprehensive Nucleus of Psychological Care architectural project is the answer to the problem "Generation of carbon footprint from construction and demolition that occurs in Hospital Architecture, in the creation of interior spaces for the improvement of mental health" the purpose of solving it is given in the first place to adapt an existing building to new mental health spaces, it is also responded to implementing the project in Boyacá-Tunja given that the municipality has presented in recent years a growth in mental health diseases due to Covid- 19 in the categories of Schizophrenia, eating disorders and anxiety, likewise the project will be located as a complement to the Tunja Local Hospital, however it responds to concepts such as Holistic Architecture, Biomimicry, Bio-construction, Macro-therapy and Sensory Perception that is on the polygon.